Noble‐Metal‐Free Ni‐MoOx Nanoparticles Supported on BN as a Highly Efficient Catalyst toward Complete Decomposition of Hydrazine Borane. Issue 12 (27th September 2018) - Li, Si‐Jia; Kang, Xia; Wulan, Ba‐Ri; Qu, Xian‐Lin; Zheng, Kun; Han, Xiao‐Dong; Yan, Jun‐Min
Abstract: Hydrazine borane (HB) has been considered as a promising hydrogen storage material due to its high hydrogen content and stability at room temperature. For the first time, a facile wet‐chemical method is developed to synthesize amorphous/low crystalline noble‐metal‐free Ni‐MoO x /BN composite as a low‐cost and high‐efficient catalyst for hydrogen generation from HB decomposition. The as‐prepared Ni‐MoO x /BN hybrid exerts 100% selective conversion and can catalyze HB complete decomposition within 5 min, corresponding to a turnover frequency (TOF) value of 600.0 h −1 at 323 K. The excellent catalytic activity may be attributed to the good dispersion, uniform particle size (≈2.6 nm), and electronic effect between nanoparticles (NPs) and support material. On further reducing the dosage of Ni, the catalyst still exhibits supreme performance, with the TOF value of 2370 h −1 ( n Ni = 0.008 mmol) at 323 K, which is the highest one among all the reported catalysts for full decomposition of HB. Thus, the excellent catalytic results provide more possibilities for the effective application of HB as a promising hydrogen storage material. Abstract : Amorphous/low crystalline noble‐metal‐free Ni‐MoO x /BN hybrid is synthesized as a low‐cost and high‐efficient catalyst for the complete decomposition of N2 H4 BH3 solution at 323 K, with the turnover frequency (TOF) value of 600 h −1 . The development of cost‐effective and high‐performance catalysts may provide more possibilities for the effective application of N2 H4 BH3 as a promising hydrogen storage material.